Managing neo-extractivism in an environmental conflict in southern Chile - Mancilla Ivaca, Nastassja Nicole (2017)
This proposal discusses the neoliberal and extractive model that has been implemented in Latin American countries due the development of the world market economy, using the case of green capitalism and the strategic use of Corporate Social Responsibility (CSR). The technique of analyzing argumentative discourses on ENDESA’s CSR was used in the context of a conflict for a hydroelectric plant in the county of Panguipulli, in southern Chile, based on semi-structured interviews conducted with governmental and local actors. Finally, discursive relations are discussed to propose that business strategies introduce and socialize this type of investments by managing neo-extractivism and particular state functions.